Development of vision, missions and objectives as foundation for business excellence - Mhd Sarif, Suhaimi (2018)
This presentation argues that business excellence initiatives have contributed to increased productivity that leads to an organization's excellence. The workshop is designed to internalize business excellence framework through strategic intent of organizations.